Prevalence and factors associated with alcohol and drug-related disorders in prison: a French national study - Reynaud Michel; Neveu Xavier; Michel Laurent; Falissard Bruno; Lukasiewicz Michael; Gasquet Isabelle (BMC, 2007)
Abstract Background Most studies measuring substance-use disorders in prisons focus on incoming or on remand prisoners and are generally restricted to drugs. However, there is evidence that substance use initiation or continuation occurs in prison, and that alcohol use is common. The aim of this study is 1) to assess prevalence of both drug and alcohol abuse and dependence (DAD/AAD) in a national randomised cohort of French prisoners, short or long-term sentence 2) to assess the risk factors associated with DAD/AAD in prison. a stratified random strategy was used to select 1) 23 prisons among the different types of prison 2) 998 prisoners. Diagnoses were assessed according to a standardized procedure, each prisoner being assessed by two psychiatrists, one junior, using a structured interview (MINI 5 plus), and one senior, completing the procedure with an open clinical interview. At the end of the interview the clinicians met and agreed on a list of diagnoses. Cloninger's Temperament and Character Inventory (TCI) was also used. Results More than a third of prisoners presented either AAD or DAD in the last 12 months. Cannabis was the most frequent drug and just under a fifth of prisoners had AAD. AAD and DAD were clearly different for the following: socio-demographic variables, childhood history, imprisonment characteristics, psychiatric comorbidity and Cloninger's TCI. Profiles of AAD in prison are similar to type II alcoholism. Conclusion Regular screening of AAD/DAD in prison, and specific treatment programmes taking into account differences between prisoners with an AAD and prisoners with a DAD should be a public health priority in prison